Concepções e ações de professores de arte/música no ensino médio integrado do IFRN - Silva, Ruânn César Cezário (2018)
The current work deals with the conceptions and actions of Art/Music teaching in two campuses of the Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Norte – IFRN. Its main objective is to investigate the conceptions and actions of Art/Music teaching in integrated Ensino Médio. And, as specific goals, it aims at comprehending the theoretical foundations of integrated training; investigating the regiments of professional and technological education; studying the conceptions and actions of the Political-Pedagogical Project-IFRN; examining the proposals of the discipline Art/Music in the Technical Integrated Courses of regular integrated Ensino Médio and in the modality EJA; ascertaining the teaching practice of Art/Music teachers; understanding the conceptions and characteristics of the teachers about the foundations that structure the pedagogical guiding documents. The methodology used in this study was multi-case research. The data analyzed were collected through documental analysis, direct observation and semi-structured interviews. The results pointed to the practical distinction between teachers, as well as to the curricular guidelines of the institution. The methods and methodologies of teachers are essentially based on practical and musical approaches, structuring the contents from the creation of shows and musical groups. These practices observed and contemplated in the teachers' discourses were quite reflexive, considering what is established as the guiding directives of the teaching of Art/Music at IFRN